Management Infertility by Hormones Replacement Therapy in Women with Polycystic Ovarian Syndrome - Sardar Qadir Omer; Tariq Waece Sadiq (Polytechnic)
Polycystic ovary syndrome (PCOS) is an endocrine-metabolic disorder characterized by multiple hormonal imbalances; the clinical presentation dominated by manifestations of hyperandrogenism, which generates short- and long-term consequences on female health sterility, infertility is one of the most alarming associated morbidities. Forty women (28.9 ± 0.8 years old) with polycystic ovarian syndrome had infertility and there were enrolled in these clinical trials and randomly allocated into two groups. Group one and Group two were given treated infertility drugs (Clomid 5 mg for 5 days) and recombinant follicle-stimulating hormone (rFSH) 75 IU for long and short duration to get pregnant. Serum testosterone, progesterone, follicle-stimulating hormone (FSH), and luteinizing hormone (LH) of both groups were measured when women diagnosed as PCOS. The results showed that women which treated by low-dose recombinant FSH 75 IU for 3 days consequently (Group one) have significant decreased LH, while progesterone and FSH significantly increased after treated by hormone therapy P ≥ 0.05 while after treatment with recombinant FSH IU for 5 days (Group two), the result showed non-significant effect as compared with the first group. Concluded: Increase pregnant rate and decrease over stimulation syndrome among infertile women associated with polycystic overian syndrome, when treated with applicated low dose and short term by rFSH hormone